Green supply chain management in Croatian companies - Opetuk, Tihomir (Array, 2018)
The scope of this paper is to present current state and trends of Green Supply Chain Management (GSCM) in Croatian companies. Due to the need for reduction of GHG emissions related to the climate change, many standards, directives, concepts, methods and models dealing with sustainability have appeared. The first part of the paper consists of an overview of GSCM where the greening diagram of GSCM is presented. The second part of the paper presents the survey which has been carried out in the Croatian business sector in view of current state and trends, barriers and drivers of the GSCM implementation. According to the results of the survey, barriers and drivers of the GSCM implementation are ranked by its significance and are compared with similar surveys carried out in the European Union (EU) and the United States of America (USA). New categorization of the drivers of the GSCM implementation is presented using the factor analysis.